New species of Eupsilocephala Krober from Australia (Diptera: Therevidae) - Winterton, Shaun L. (Zootaxa, 2006)
The stiletto fly genus Eupsilocephala Kröber is a member of the Taenogera genus-group endemic to Australia. Two new species of this rarely collected genus, Eupsilocephala albodorsalis sp. nov. and Eupsilocephala sulphurea sp. nov., are described.